Poverty and its Relations to Some Social Variables (Children in the Primary Stage as a Model) (Journal of the College of Education for Women, 2018)
The phenomenon of poverty is one of the most important phenomena facing the world at large. Despite the tremendous technological progress witnessed by mankind and despite the unprecedented high levels of world economic production, poverty remains the greatest challenge facing the world. Statistics and studies have shown that poverty is caused by several problems: (health, social, economic, educational, etc.) These problems are obstacles to the ability to obtain employment opportunities, which leads in the beginning to the growth phenomenon of unemployment, and ultimately to the growth of poverty.The results of a range of research in the field of psychology have confirmed that children from poor homes suffer from a high level of stress and stress, compared to their peers from children of average or high economic status. The results also suggest that these children may suffer at an early age of psychological stress, which usually begins at the age of three and continues to the advanced stages of age, whatever the condition of the individual. Psychological stress can also lead to other family problems, such as abusive parenting, poor child health, and low academic attainment.The current study aimed to identify the relationship of poverty (low economic level) among primary school students according to the variables: (level of achievement, health status, social status). Then a questionnaire was constructed to identify the way poverty related to the variables mentioned above. A sample of 100 students in primary school was also withdrawn to apply the research tool.